Tarot images and spiritual education: the three I’s model - Semetsky, Inna (2011)
The paper presents education as a process of human development toward becoming our authentic Selves and posits the Tarot hermeneutic as one of the means of holistic, spiritual education. As a system of images and symbols, Tarot encompasses the three I’s represented by intuition, insight and imagination in contrast to the three R’s of traditional formal schooling. If teachers want to foster intuitive abilities in their students, they need to first develop this capacity in themselves using the available cultural practice of Tarot. Through Tarot symbolism we can become aware of the deep meanings of human experiences that may be hiding in the unconscious at the soul level. The informal ‘school of life’ embodied in images unveils the dimension of inner knowledge or gnosis that exceeds the factual knowledge of the external world but reaches toward the Imaginal world due to intuitive mode of perception.
Keywords: Imagination; Intuition; Nel Noddings’ ethics of care; philosophy of education; Tarot symbolism